Hubungan Pengetahuan Dengan Kepatuhan Minum Obat Pada Pasien Diabetes Tipe II di RSPAD Gatot Soebroto - Raihan Akbar Darmawan; Rika Revina; Retno Yulianti (Indonesian Journal of Pharmaceutical Education, 2023)
Diabetes mellitus is a chronic disease requires a tight management. Two of the factors that facilitate medication adherence are information and knowledge. This research objective was to find the relation between diabetes knowledge and medication adherence degree of type II Diabetes Mellitus at RSPAD Gatot Soebroto. The design of this research was analytic observational with the cross-sectional method. The populations of this research were the type II DM outpatients who went to RSPAD Gatot Soebroto on May 2023 with the total of samples were 64 people. The instruments that were used to measure knowledge and the medication adherence degrees were the Diabetes Knowledge Questionnaire (DKQ-24) and the Morisky-Green Levine Medication Adherence Scale (MGLS). Respondents who have sufficient level of knowledge amounted to 53.1%. Respondents who had a moderate level of medication adherence amounted to 57.8%.Â  The P value obtained from the result of Somerâ€™s d Gamma test was 0.6. These can be interpreted as no significant relation between knowledge about diabetes and medication adherence degree of Diabetes Mellitus type II at RSPAD Gatot Soebroto.